Improving Special Education Student Reading Skills Through Fast Reading Methods - Farah Zurah binti Mohd Yusof (Best Practices in Disability-Inclusive Education, 2022)
Reading is an essential part of human life. Reading abilities are also a gateway to knowledge. Pupils' reading weaknesses cause them to misinterpret what is read, making it difficult for them to follow the learning process. It also has a negative impact on individual achievement in all courses. Inappropriate reading methods allow children to become bored quickly, lose interest, and fall asleep while reading. Program Celik Membaca a best practice conducted with the intention of helping Students with Special Educational Needs (SSEN) at Sekolah Kebangsaan Pernu (Pernu National School), Melaka to overcome their reading difficulties. Anugerah 2 class students who follow KSSRPK Year 2 are the target group for this practice's implementation. The data gathered using qualitative methods such as observation and interviews. The practise results show that the implementation of this practice successfully improves SEN reading skills and increases their confidence in a variety of activities, both in and out of class.